Corticosterone and progesterone differentially regulate HPA axis and neuroimmune responses to stress in male rats. (3rd July 2020) - Hueston, Cara M.; Deak, Terrence
Abstract: In response to stressor exposure, expression of the inflammatory cytokine interleukin-1β (IL-1) is increased within the paraventricular nucleus of the hypothalamus (PVN). Surgical removal of the adrenal glands (ADX) potentiated stress-induced IL-1 expression, suggesting a role for adrenal-derived hormones in constraining stress-evoked increases in IL-1. While corticosterone (CORT) is a primary factor inhibiting IL-1 expression, progesterone (PROG) is also released by the adrenal glands in male rats in response to stress and also has potent anti-inflammatory properties. This series of studies first established doses of CORT and PROG that adequately recapitulate the normal stress-induced rise, and then tested for individual and combined roles of CORT and PROG in mitigating stress-induced expression of inflammatory genes. We found that CORT injection alone attenuated ADX-induced increases in IL-1 expression and normalized the HPA axis response to stress. In general, PROG replacement had little effect on changes in HPA axis responsivity or stress-induced inflammatory measures. When CORT and PROG were co-administered, a small effect on expression of the decoy receptor, IL-1R2 was observed, suggestive of an anti-inflammatory response. Overall, these results suggest that although CORT is likely to be the primary stress-related hormone responsible for constraining cytokine expression evoked by stress, CORT and PROG may exert certain combined actions that temper stress-induced neuroinflammation. LAY SUMMARY: Exposure to stress promoted expression of inflammation-related genes in the PVN and BNST. This inflammation was mainly suppressed by the adrenal hormone corticosterone, whereas progesterone had a smaller role in mitigating post-stress inflammation.